MOSQUE DA'WAH COMMUNICATION MANAGEMENT IN FOSTERING MILLENNIAL CONGREGATION (CASE STUDY OF NURUL IMAN MOSQUE BLOK M SQUARE - Husnan Nurjuman; Ronny Yudhi Septa Priana; Dewi Nursyamsiah (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
The aim of this study was to analyze the da’wah activities carried out by DKM Nurul Iman. The research used the management activities POLC (Planning, organizing, leading, and controlling) by Stephen Robbins. Used a qualitative-descriptive approach with a case study method. Data collections are derived from interviews, observations, literature studies, the social media activities of Nurul Iman Blok M Square Mosque, and other supporting documents. The results showed that the dakwah communication management activities carried out by DKM Nurul Iman were due to cooperation with da'wah partners, such as preachers, majelis taklim, and study communities managed by young people (millennials). In every stage of the activity process, starting from planning, organizing, leadership, and controlling activities, DKM Nurul Iman always invites da'wah partners to participate. As a facilitator of dawah activities, the mosque collaborates with millennial creative ideas to produce da'wah material that can change the tendency of negative millennial behavior to be more conservative in a bandage of Islamic values.